Apolipoprotein M suppresses the phenotypes of IgA nephropathy in hyper‐IgA mice. Issue 4 (10th January 2019) - Kurano, Makoto; Tsuneyama, Koichi; Morimoto, Yuki; Nishikawa, Masako; Yatomi, Yutaka
ABSTRACT: Because the association between sphingosine 1‐phosphate (S1P)/apolipoprotein M (ApoM) and chronic kidney diseases has not been established, we investigated the involvement of S1P/ApoM in the phenotypes of IgA nephropathy in hyper‐IgA (HIGA) mice. The overexpression of ApoM in adenoviral gene transfer ameliorated the phenotypes of IgA nephropathy in HIGA mice, whereas the knockdown of ApoM with siRNA caused deterioration. When ApoM‐overexpressing HIGA mice were treated with VPC23019, an antagonist against S1P receptor 1 (S1P1) and 3 (S1P3), we observed that the protective effects of ApoM were reversed, whereas JTE013, an antagonist against S1P2, did not inhibit the effects. We also found that S1P bound to albumin accelerated the proliferation of MES13 cells and the fibrotic changes of HK2 cells, which were inhibited by JTE013, whereas S1P bound to ApoM suppressed these changes, which were inhibited by VPC23019. These results suggest that S1P bound to ApoM possesses properties protective against the phenotypes of IgA nephropathy through S1P1 and S1P3, whereas S1P bound to albumin exerts deteriorating effects through S1P2. ApoM may be useful as a therapeutic target to treat or retard the progression of IgA nephropathy.—Kurano, M., Tsuneyama, K., Morimoto, Y., Nishikawa, M., Yatomi, Y. Apolipoprotein M suppresses the phenotypes of IgA nephropathy in hyper‐IgA mice. FASEB J. 33, 5181–5195 (2019). www.fasebj.org